Petits arrangements avec le vivant dans le bocage pavillonnaire - Pauline Frileux; Élodie Paillocher (Développement Durable et Territoires)
People living in housing developments have an impact on their environment while gardening. As a matter of fact, they introduce horticultural and exotic plants, favour a selection of wild animal and vegetal species, suppress others. They also interfere with the cycle of matter: clearing away green waste, introducing fertilizer, watering, etc. Two main tendencies can be observed among gardeners: scrupulously weeding addict ones and eco-focused. Clean maintenance guides the way of gardening and relations to living, but practices are gradually changing thanks to environmental politics, nature organizations and legislation. The neat garden still acts as a model, but the recent keen interest in domesticated herbivores – under environmental motivations (to reduce waste), and edible productions could be the fore-runner of an agricultural and ecological recovering of the housing bocage.